Pengaruh Penambahan Kulit Durian Pada Pengolahan Limbah Perkebunan Karet Dengan Metode Karbonisasi Menjadi Briket Di Wilayah Polokarto - Maria, Ernastin (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
Since the abundant rubber plantation waste in the Polokarto area has not been optimally utilized and is decomposing in the field, it is necessary to process it, for example, into biobriquettes using the carbonization method with a mixture of durian skin. The purpose of this research is to reduce rubber plantation waste by trying to incorporate durian skin into briquettes using the carbonization method and determining how much economic profit is obtained. According to the result obtained of this study's analysis, the best briquettes were made with a 50%:50% composition ratio of rubber plantation waste and durian skin, which produced an ash content of 13.2643%, a boiling time of 13.14 minutes, and no combustion smoke. It takes 4522 kg of briquettes to calculate using the break event point (BEP) method, and they are sold in about 5.12 months. According to the calculations, the NPV value is Rp. 37.872340, which is relatively high than the project cost value. The IRR result is 28 % based on the IRR calculation. The business is considered profitable and feasible to run because the IRR is greater than 15%.